Rotorcraft pre-design activities at DLR - Results, status and outlook - - Lier, M.; Kohlgrüber, D.; Krenik, A.; Kunze, P.; Lützenburger, M.; Schwinn, D. (My University, 2014)
The German Aerospace Center (DLR) is currently developing an integrated and automated tool for helicopter preliminary design and evaluation. To support the design process and the evaluation task, an integrated rotorcraft design and evaluation toolbox covering the conceptual and preliminary design stages was developed. Further work will extend this toolbox with special regard to novel rotorcraft configurations and includes the development of suitable models for the interaction of different components of the helicopter. The paper gives an overview of recent activities in rotorcraft design as well as detailed descriptions of the process chain and software modules for rotorcraft preliminary design developed at DLR. First results of the integrated toolbox are shown. Furthermore the current activities at DLR regarding the topic and an outlook on planned activities are presented.